Új Tengeri Selyemút Délkelet-Ázsiában a Fülöp-szigetek példája a Dutertenomics céljainak tükrében - Klemensits Péter (Geopolitikai szemle, 2020)
One of the major elements of the One Belt, One Road (OBOR) initiative launched by China in 2013 is the concept of the 21st Century Maritime Silk Road. The aim of this mega project is to revolutionize deep-sea trade from Southeast Asia through Africa to Europe, and to put the participating countries on the track of economic development with the help of the infrastructural developments along the coastline. At the same time, it is also significant in a geopolitical sense because it has become the decisive element of Chinese foreign policy, furthermore in the case of ASEAN countries, it has a greater strategic goal: reinforcing China’s influence in the region enjoys priority in the field of both economy and politics. Based on an interdisciplinary approach, the paper will provide a summary of the 21st Century Maritime Silk Road and especially the Philippines’ place in the Chinese plans. It will then discuss in detail the aims of the Duterte administration, in political and economic terms alike (Dutertenomics). The results and the anticipated consequences of the new prosperous partnership between the Philippines and China – namely the agreements and the initiated projects – will also be assessed. According to the paper’s conclusion, Chinese investments can make a great contribution to the development of the Philippines, but the successful realization of Duterte’s plans will depend on the skills of his government in managing very serious foreign and internal political challenges in the remaining 3 years.